Dextromethorphan Inhibits the Glutamatergic Synaptic Transmission in the Nucleus Tractus Solitarius of Guinea Pigs - Yoshiaki Ohi; Saori Tsunekawa; Akira Haji (Elsevier, 2011)
Abstract.: Dextromethorphan (DEX) is a widely used non-opioid antitussive. However, the precise site of action and its mechanism were not fully understood. We examined the effects of DEX on AMPA receptor-mediated glutamatergic transmission in the nucleus tractus solitarius (NTS) of guinea pigs. Excitatory postsynaptic currents (evoked EPSCs: eEPSCs) were evoked in the second-order neurons by electrical stimulation of the tractus solitarius. DEX reversibly decreased the eEPSC amplitude in a concentration-dependent manner. The DEX-induced inhibition of eEPSC was accompanied by an increased paired-pulse ratio. Miniature EPSCs (mEPSCs) were also recorded in the presence of Cd2+ or tetrodotoxin. DEX decreased the frequency of mEPSCs without affecting their amplitude. Topically applied AMPA provoked an inward current in the neurons, which was unchanged during the perfusion of DEX. BD1047, a σ-1-receptor antagonist, did not block the inhibitory effect of DEX on the eEPSCs, but antagonized the inhibition of eEPSCs induced by SKF-10047, a σ-1 agonist. Haloperidol, a σ-1 and -2 receptor ligand, had no influence on the inhibitory action of DEX. These results suggest that DEX inhibits glutamate release from the presynaptic terminals projecting to the second-order NTS neurons, but this effect of DEX is not mediated by the activation of σ receptors. Keywords:: dextromethorphan, nucleus tractus solitarius, excitatory postsynaptic current, patch clamp, σ receptor